Genes for respiratory chain proteins and ribosomal RNAs are present on a 16-kilobase-pair DNA species from Chlamydomonas reinhardtii mitochondria. - Boer, P H (1985)
We have used heterologous hybridization and DNA sequence analysis to determine whether the 16-kilobase-pair (kbp) DNA from Chlamydomonas reinhardtii mitochondria is the functional equivalent of mtDNA in other eukaryotes. Restriction fragments corresponding to a continuous internal stretch spanning 75% of the 16-kbp DNA have been cloned and mapped, and regions hybridizing with probes specific for the cytochrome oxidase subunit I [CytOx I (acronym COI)] and apocytochrome b (Cyt b) genes of yeast and the mitochondrial 26S and 18S rRNA genes of wheat have been identified. Sequence analysis has verified the presence of CytOx I and the large and small subunit rRNA genes in the C. reinhardtii 16-kbp DNA. In the region of the 16-kbp DNA corresponding to exon 4 in the yeast CytOx I gene, the derived amino acid sequence is 61% and 63% identical with the CytOx I amino acid sequences of yeast and human mitochondria, respectively. Notably, tryptophan is specified by TGG rather than by TGA in this section of the C. reinhardtii CytOx I gene. A probe from the CytOx I region of the 16-kbp DNA hybridizes only with this 16-kbp DNA in Southern blots of total cellular DNA from C. reinhardtii but with a larger DNA species in the total cellular DNA of C. moewusii and C. eugametos--two species that lack a 16-kbp DNA. These observations provide evidence that C. reinhardtii 16-kbp DNA comprises at least part of the mitochondrial genome of this organism and that a homologous DNA exists in other species of Chlamydomonas.